1989
DOI: 10.1080/00014788.1989.9729389
|View full text |Cite
|
Sign up to set email alerts
|

The Information Content of Cash Flow Figures

Abstract: This paper investigates the link between earnings and share prices for a sample of UK companies for the years 1961 to 1977. Three measures of earnings were used: the traditional historical cost accounting return and two which were closer to cash flow measures. The strength of the link between earnings and cumulative abnormal returns was investigated relative to the level of inflation. The results indicate that, while there is substantial information content in the traditional historical cost rate of return, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 12 publications
(10 reference statements)
4
25
0
1
Order By: Relevance
“…They concluded that both specifications are important in explaining stock returns but the differenced model yield higher ERC's compared to the return model. This finding agrees with studies by Martikainen et.al (1991), Board and Day (1989), Alford et.al (1993) and Harris et.al (1994).…”
Section: Consistent Tosupporting
confidence: 93%
“…They concluded that both specifications are important in explaining stock returns but the differenced model yield higher ERC's compared to the return model. This finding agrees with studies by Martikainen et.al (1991), Board and Day (1989), Alford et.al (1993) and Harris et.al (1994).…”
Section: Consistent Tosupporting
confidence: 93%
“…The focus on cash flows from operations may be the serious limitation of this study. Simons (1992); Charitou and Vafeas (1998);and Board and Day (1989) provided similar conclusion to the study of Cheng, Liu and Schaefer (1997).…”
Section: Evidence On Incremental Information Content Of Cash Flowssupporting
confidence: 85%
“…However, Ali and Pope (1995) doubted the validity of the three performance measures employed by Board and Day (1989). Ali and Pope extended Board and Day's study by incorporating some recent innovations in the specifications of earnings-returns model.…”
Section: Evidence On Incremental Information Content Of Cash Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others are saying that there is a lower correspondence in the evolution cash flowmarket price than in the one which relates earnings to the price on the stock market. In another study, Board and Day (1989) sustain the reduced amount of information expressed through cash flows, but conclude, however, that there is a high informational content in the traditional rates of return expressed at historical values. The content is also reflected in the evolution of shares on the stock market.…”
Section: Introductionmentioning
confidence: 90%